2019
DOI: 10.1002/anie.201908274
|View full text |Cite
|
Sign up to set email alerts
|

A One‐Dimensional π–d Conjugated Coordination Polymer for Sodium Storage with Catalytic Activity in Negishi Coupling

Abstract: p-d Conjugated coordination polymers (CCPs) have attracted muchattention for various applications,although the chemical states and structures of many CCPs are still blurry. Now,aone-dimensional (1D) p-d conjugated coordination polymer for high performance sodium-ion batteries is presented. The chemical states of the obtained coordination polymer are clearly revealed. The electrochemical process undergoes at hree-electron reaction and the structure transforms from C=Nd ouble bonds and Ni II to CÀNs ingle bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
178
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 85 publications
5
178
1
Order By: Relevance
“…In a similar system, it has been confirmed that Ni II in a coordination polymer can be reduced to Ni I even though Ni II was stable in the compound. Thus, an additional one‐electron transfer is enabled during the electrochemical reaction . Notably, the applied voltage range is greatly important for the contribution of Cu because Cu II can be reduced to Cu 0 at a low working potential .…”
Section: Resultsmentioning
confidence: 99%
“…In a similar system, it has been confirmed that Ni II in a coordination polymer can be reduced to Ni I even though Ni II was stable in the compound. Thus, an additional one‐electron transfer is enabled during the electrochemical reaction . Notably, the applied voltage range is greatly important for the contribution of Cu because Cu II can be reduced to Cu 0 at a low working potential .…”
Section: Resultsmentioning
confidence: 99%
“…[37] The high electrical conductivity of Ni-BTA can be attributed to the delocalization of electrons in the -d systems, in which nickel nodes can mediate efficient conjugation pathways between electroactive organic linkers. [31,35,38,39] Encouraged by the large surface area and high conductivity of Ni-BTA 1D -d CCP, we envision that the Ni-BTA nanowire film would possess superior electrochemical and electrochromic performance simultaneously. To validate the hypothesis, cyclic voltammetry (CV) was measured using a three-electrode spectroelectrochemical cell (Ni-BTA nanowires on conductive FTO substrate as a working electrode, Ag/AgCl as a reference electrode, Pt foil as a counter electrode, and conventional 1 m KOH aqueous solution as the electrolyte).…”
Section: Doi: 101002/advs201903109mentioning
confidence: 99%
“…The normalized X-ray absorption near edge structure (XANES) spectra of Ni-BTA nanowire film in the initial and 3rd cycle colored and bleached states are shown in Figure 4c. The XANES spectrum of the initial Ni-BTA film presents a shoulder peak at 8340 eV, which can be ascribed to Ni(II) in a low spin square planar configuration, [35,54] as shown in Figure 1a. Interestingly, in the colored state, the absorption peak at 8340 eV is absent evidencing that the oxidation state of Ni is significantly different.…”
Section: Doi: 101002/advs201903109mentioning
confidence: 99%
“…[18,19] Romansand Wangs groups synthesized one-dimensional metal-organic polymers (MOPs) with 1,2,4,5-benzenetetramine as the organic ligand for LIBs and SIBs,r espectively. [20,21] Theb onds formed between the organic ligands and metal ions and the delocalized electron distributions endow the chemical and electrochemical stability of the MOPs,w hich are essential for the reversible redox reactions of organic electrode materials. Functionalization of the organic ligands and tuning the metalligand bonds allow for the versatile features of MOPs,such as multiple redox centers,h igh electron conduction, and good structure stability,e tc., desirable for organic electrode materials.…”
mentioning
confidence: 99%
“…An extra peak at 399.6 eV in the N1s XPS spectra of Ni-TABQ in Figure 1c,compared to that at 398.0 eV of TABQ,is attributed to the quinoid imine (C=N), along with the benzoid amine (C À N). [21] This leaves unpaired electrons around N atoms,w hich are delocalized in the conjugation system in Figure 1a.Solid-state 13 Cnuclear magnetic resonance (NMR) spectrum of Ni-TABQ in Figure 1d shows two major 13 Cs ignals at 96.6 and 162.6 ppm, which correspond to the carbons in the CN and CO bonds, [20,23] respectively.T he electron paramagnetic resonance (EPR) spectrum of Ni-TABQ is shown in the Supporting Information, Figure S5, where as trong signal with g-factor value of 1.9992 is originated from the unpaired electrons around the coordination bonds.I ti sc lear that Ni-TABQ is formed with Ni 2+ bound to four Natoms of two TABQ in each repeated unit in Figure 1a.…”
mentioning
confidence: 99%